Particle physics in laboratory, space and universe : (World Scientific, 2005)
This volume brings together the latest developments within a wide spectrum of topics in particle physics. Covering both theoretical and experimental aspects, areas such as neutrino and astroparticle physics, tests of the Standard Model and beyond, heavy quark physics, non-perturbative QCD, quantum gravity effects and cosmology, physics at the future accelerators, etc. are discussed.